Biology of Helopeltis Theivora (Hemiptera: Miridae) on Acasia Mangium Willd - Rustam, Rusli; Pangky Sucahyono, Muhamad; Salbiah, Desita (International Journal on Advanced Science, Engineering and Information Technology, 2014)
One of the problems in the management of A. mangium is Helopeltis sp. attack. It is important to study about the biology of Helopeltis sp because current research and report of biology of Helopeltis theivora on A. mangium is very limited. The research was aimed to know the biology of H. theivora. The observations of pest biology were carried out in twenty repititions. Then the result was arranged into the insect life-table in order to easy analysis of the observation. The parameters measured were the number of eggs, fecundity, longevity of nymphs and adult insects.  An adult insect had the longest life span. The female and male ratio was 1:1,43. The Female maximum life span is 15 days. The total eggs produced by a female insect was 46,74. H. theivora had a high reproductive capacity with R0 at 11.40, T 28.09, r 0.09 and  Î» 1.09.